KLASİK TÜRK EDEBİYATINDA ÎD VE ÎDİYYELER - ÖZTEK, GÜLSÜM (Fırat Üniveristesi, 2012)
Klasik Türk Edebiyatı şairleri, Türk toplumunda her zaman oldukça önemli bir yere sahip olan dini bayramları ve bayramlarda yaşananları, divanlarda birçok beyitte dile getirmektedirler. Ancak dini bayramlar özellikle kasidelerin giriş bölümlerinde, kıta, gazel ve şarkı gibi nazım şekilleriyle yazılan şiirlerin bir kısmında belli başlı bir tema olarak işlenmektedir.Îdiyye/bayram şiirlerinin kendine has bir formu vardır. Kaside ve kıta nazım şekliyle yazılan îdiyyelerde konunun işleniş ve sunumu bakımından benzerlikler görülmektedir. Bunlar genellikle hilal tasviriyle başlamakta ?medhiye? bölümünde övülen kişinin nitelikleriyle bayram ve bayramlarda yaşananlar arasında çeşitli benzetme ve mecazlarla ilgi kurulur.Anahtar Kelimeler: Îd, Îdiyye, Sevgili, Aşk, Hasret, Ayrılık

Classical Turkish Literature Poets express religious eids and events happened on eids which have a big importance for Turkish society, on many couplets (beyit) in divans. However, eids are expressed as a main theme in some pieces of poems which written in verse like sections, gazels and songs, esspecially on entrance section of kasidas.Eid poems have their own and original form. In some eid poems which versely written in kasida and section forms, there are similarities in terms of processing and presentation of subject. These are usually start with a description of crescent moon; various analogy and metaphores get related between personality of the person who is praised on the section of ?mehdiye? (panegyric) and the eids or events happened on eids.Key Words: Eid, Eid Poem (İdiyye), Beloved, Love, Longing, Seperation.
Eids and ?idiyye?s in Turkish literature
Keywords: Türk Dili ve Edebiyatı